Performance analysis and simulation verification of S-MAC for wireless sensor networks. (November 2016) - Rao, Yuan; Cao, Yi-ming; Deng, Cheng; Jiang, Zhao-hui; Zhu, Jun; Fu, Lei-yang; Wang, Ru-chuan
Highlights: We propose one state machines model for S-MAC protocol. We use a probabilistic model to analyze the latency and stability performances. Sleeping mechanism does have negative impacts on the latency and stability performances. Adaptive listening mechanism does optimize the latency and stability performances. Appropriate dutyCycle can be used to further improve the latency and stability. Abstract: As a typical media access protocol, S-MAC has drawn much attention in the past decades. However, most of the attention focuses on energy efficiency, but fails to guarantee QoS performance. Firstly, we develop one state machines model and elaborate on the states' transition processes of S-MAC. Secondly, combining our state machines with the specific parameters of S-MAC, we propose an analytical probabilistic model to investigate the latency and stability performances of S-MAC employing three different mechanisms: without sleeping mechanism, with sleeping mechanism, and with adaptive-listening mechanism. Also we analyze the latency and stability performances of S-MAC with different dutyCycle values. This research shows two interesting results: 1) Sleeping mechanism inside S-MAC does have negative impacts on its latency and stability; fortunately, adaptive listening mechanism can optimize them to some extent. 2) Latency and stability performances of S-MAC can be further improved through manipulating dutyCycle values. The simulations in NS2 exhibit consistent results with those obtained from our analytical probabilistic model.